Iron atom substitution-zinc sulfide negative electrode material, preparation method thereof and potassium ion battery
The iron atom-substituted zinc sulfide negative electrode material was prepared by co-precipitation-annealing method, which solved the problem of poor performance of zinc-based sulfide negative electrode material, and achieved high specific capacity, excellent charge and discharge rate performance and long cycle stability.
Patent Information
- Application Number
- CN202411808084.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Commercial graphite negative electrode materials have poor performance due to slow ion transport, low theoretical capacity and large volume changes, which are difficult to meet the needs of high energy density. The zinc-based sulfide negative electrode has problems such as difficulty in ion diffusion, poor conductivity, easy crystal lattice collapse and polysulfide shuttle, resulting in a sharp drop in the specific capacity of the battery and poor charging and discharge rate performance.
The iron atom-substituted zinc sulfide negative electrode material was prepared by a combined method of coprecipitation-annealing. The Fe atoms replace the position of some Zn atoms in the crystal structure of ZnS, improve the intrinsic conductivity of ZnS, reduce the activation energy of the electrochemical reaction, and improve the conductivity and structural stability through nitrogen-doped carbon coating and polyaniline coating.
The specific capacity and charge and discharge rate performance of the negative electrode of the potassium ion battery are improved, the mechanical stress caused by the large K+ embedding is alleviated, the ZnS lattice structure is stabilized, and the long cycle stability and high rate performance are ensured.
Smart Images

Figure CN119284941B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of potassium ion batteries, and in particular to an iron atom substituted zinc sulfide negative electrode material, a preparation method thereof, and a potassium ion battery. Background Art
[0002] Traditional lithium-ion batteries are expensive due to the scarcity of lithium resources, which limits their application in the field of stationary energy storage. Potassium-ion batteries (PIBs) are an ideal alternative to lithium batteries due to their rich potassium content and low cost. Their high energy density comes from the low redox potential of potassium (-2.92 V). However, commercial graphite anodes have poor performance due to slow ion transport, low theoretical capacity, and large volume changes, making it difficult to meet the demand for high energy density. Therefore, it is crucial to develop high-performance potassium-ion battery anode materials.
[0003] Transition metal sulfides (TMSs) have become one of the candidates for high-energy PIBs anodes due to their high theoretical capacity due to their multi-electron reaction mechanism. The performance of TMSs is closely related to their ion / electronic state and crystal structure. ZnS, as an important TMSs, has attracted much attention due to its low cost, non-toxicity and low carbon. However, the large lattice volume change and insufficient inherent conductivity of zinc-based sulfide anodes lead to problems such as difficult ion diffusion, poor conductivity, easy lattice collapse and polysulfide shuttling when used in PIBs, resulting in a sharp drop in battery specific capacity and poor charge and discharge rate performance. Summary of the invention
[0004] The purpose of this application is to provide an iron atom substituted zinc sulfide negative electrode material, a preparation method thereof and a potassium ion battery to improve at least one of the above technical problems. This application achieves the above purpose through the following technical solutions.
[0005] In a first aspect, an embodiment of the present application provides a method for preparing an iron atom-substituted zinc sulfide negative electrode material, comprising:
[0006] S1: Mix ammonium ferric citrate, L-cysteine and deionized water to form solution A. The concentration of ammonium ferric citrate in solution A is 2-5 mmol / L -1 , the concentration of L-cysteine is 0.24-0.3 molL -1 ; Mix zinc nitrate hexahydrate and deionized water to form solution B, the concentration of zinc nitrate hexahydrate in solution B is 90-100mmolL -1 ; Dimethylimidazole and deionized water were mixed evenly to form solution C, the concentration of dimethylimidazole in solution C was 0.6-0.7 molL -1 ;
[0007] S2: uniformly mixing solution A, solution B and solution C in a weight ratio of 1:2:2-1.5:2:2 to obtain a precursor solution, and collecting the precursor powder after centrifuging the precursor solution;
[0008] S3: annealing the precursor powder at 700-1000° C. for 2-4 h in an inert atmosphere to obtain an iron atom-substituted zinc sulfide negative electrode material.
[0009] In one embodiment, the inert atmosphere in step S3 is an argon atmosphere or a nitrogen atmosphere.
[0010] In one embodiment, step S3 includes heating the precursor at 2-5°C min under an argon atmosphere. -1 The temperature is increased to 500-550°C and kept at this temperature for 2-4 hours, and then increased to 700-1000°C and kept at this temperature for 2-4 hours.
[0011] In one embodiment, step S2 further comprises mixing solution A, solution B and solution C in a weight ratio of 1:2:2-1.5:2:2 to obtain a precursor solution, continuing stirring for 1-2 hours, and aging at room temperature for 3-5 days.
[0012] In one embodiment, the preparation method further includes step S4, which includes: preparing a polyaniline ethanol solution with a concentration of 5%-10%wt, mixing the iron atom substituted-zinc sulfide negative electrode material and the polyaniline ethanol solution in a weight ratio of 1:20-1:25, stirring for 2-3 hours and simultaneously performing ultrasonic treatment, separating the mixed solution by centrifugation, collecting the coated powder, washing and drying to obtain the polyaniline-coated iron atom substituted-zinc sulfide negative electrode material.
[0013] In a second aspect, the present application provides an iron atom substituted-zinc sulfide negative electrode material, which is prepared according to the preparation method of the iron atom substituted-zinc sulfide negative electrode material of the first aspect, and includes nitrogen-doped carbon-coated doped zinc sulfide, and the doped zinc sulfide includes zinc sulfide and iron atom-doped zinc sulfide.
[0014] In one embodiment, the iron atom substituted-zinc sulfide negative electrode material has a hollow spherical morphology and a diameter of 550-650 nm.
[0015] In one embodiment, in the doped zinc sulfide, the proportions of Fe, Zn, and S atoms are 5-8%, 47-50%, and 44-46%, respectively.
[0016] In one embodiment, the nitrogen-doped carbon-coated doped zinc sulfide outer layer is coated with polyaniline.
[0017] In a third aspect, the present application further provides a potassium ion battery, which includes a positive electrode and a negative electrode, wherein the negative electrode of the potassium ion battery is prepared by the iron atom-substituted zinc sulfide negative electrode material of the second aspect.
[0018] The method provided in the embodiment of the present application is to prepare the iron atom-substituted zinc sulfide negative electrode material for potassium ion batteries. Through the combined method of coprecipitation-annealing, Fe atoms can replace the positions of some Zn atoms in the crystal structure of zinc sulfide, thereby improving the intrinsic conductivity of ZnS, reducing the activation energy of the electrochemical reaction, and generating a large number of S vacancies to induce the generation of a built-in electric field, accelerating K + The diffusion rate in the negative electrode material is improved, thereby improving the specific capacity and charge-discharge rate performance of the battery when it is used as the negative electrode of potassium ion batteries. In addition, the optimized ZnS realizes the redistribution of charges around the metal-sulfur bond, increases the bond energy of the Zn-S bond and stabilizes the ZnS lattice structure, greatly alleviating the problem caused by large K + The uneven internal mechanical stress caused by embedding alleviates the capacity degradation problem caused by lattice collapse. Potassium-ion batteries use iron atoms to replace zinc sulfide negative electrode materials. On a macro scale, the carbon encapsulation strategy formed after amino acid annealing effectively improves its conductivity. Its stable hollow structure effectively alleviates the mechanical strain stress generated during potassium storage, thereby improving its structural stability during potassium storage, and achieving excellent long-cycle stability even at high rates. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions in the implementation modes of the present application, the drawings required for use in the description of the implementation modes will be briefly introduced below. Obviously, the drawings described below are only some implementation modes of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0020] Figure 1 The SEM image of Fe-ZnS@C of Example 1 of the present application is shown.
[0021] Figure 2 The TEM image and electron diffraction image of Fe-ZnS@C of Example 1 of the present application are shown.
[0022] Figure 3 The energy spectrum elemental image analysis diagram of Fe-ZnS@C of Example 1 of the present application is shown.
[0023] Figure 4The synchrotron radiation-proven wavelet transform (WT) analysis contour map of Fe-ZnS@C of Example 1 of the present application is shown, where (a) is the continuous Cauchy wavelet transform k3-weighted X-ray absorption fine structure spectrum (EXAFS) of Fe foil, and (b) is the continuous Cauchy wavelet transform k3-weighted X-ray absorption fine structure spectrum (EXAFS) of Fe-ZnS@C.
[0024] Figure 5 The SEM image of PANI@Fe-ZnS@C of Example 6 of the present application is shown.
[0025] Figure 6 The figure shows the rate cycle performance of batteries made of the negative electrode materials of Example 1 and Comparative Example 2 of the present application.
[0026] Figure 7 The high current density cycle performance diagram of the battery made of Fe-ZnS@C in Example 1 of the present application is shown.
[0027] Figure 8 The full cell rate performance diagram of the battery made of Fe-ZnS@C in Example 1 of the present application is shown. DETAILED DESCRIPTION
[0028] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the implementation mode of the present application will be clearly and completely described below in conjunction with the drawings in the implementation mode of the present application. Obviously, the described implementation mode is only a part of the implementation mode of the present application, not all the implementation modes. Based on the implementation mode in the present application, all other implementation modes obtained by those skilled in the art without making creative work are within the scope of protection of the present application.
[0029] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0030] The present application provides a potassium ion battery iron atom substituted zinc sulfide negative electrode material prepared by the following steps:
[0031] In a first aspect, an embodiment of the present application provides a method for preparing an iron atom-substituted zinc sulfide negative electrode material, comprising:
[0032] S1: Mix ammonium ferric citrate, L-cysteine and deionized water to form solution A. The concentration of ammonium ferric citrate in solution A is 2-5 mmol / L-1 , for example, can be 2mmolL -1 , 2.5mmolL -1 , 3.2mmolL -1 ; The concentration of L-cysteine is 0.24-0.3 molL -1 For example, it can be 0.28 molL -1 , 0.29mmolL -1 ; Mix zinc nitrate hexahydrate and deionized water to form solution B, the concentration of zinc nitrate hexahydrate in solution B is 90-100mmolL -1 Exemplarily, it can be 92mmolL -1 、95mmolL -1 , 100mmolL -1 ; Dimethylimidazole and deionized water were mixed evenly to form solution C, the concentration of dimethylimidazole in solution C was 0.6-0.7 molL -1 , for example, can be 0.65 molL -1 ;
[0033] S2: Mix solution A, solution B and solution C in a weight ratio of 1:2:2-1.5:2:2. For example, the ratio may be 1.3:2:2. After mixing, a precursor solution is obtained. Stirring is continued for 1-2 hours, and aging is performed at room temperature for 3-5 days.
[0034] S3: Precursor powder is heated at 2-5℃min in argon or nitrogen atmosphere. -1 The temperature is increased to 500-550°C and kept at this temperature for 2-4 hours, and then increased to 700-1000°C and kept at this temperature for 2-4 hours. For example, the temperature can be increased to 750°C, 800°C, 900°C, or 1000°C.
[0035] The iron atom-substituted zinc sulfide negative electrode material for potassium ion batteries provided in an embodiment of the present application is a nitrogen-doped carbon-coated doped zinc sulfide through a combined method of coprecipitation-annealing. In the doped zinc sulfide, Fe atoms can replace the position of some Zn atoms in the crystal structure of ZnS. In one embodiment, in the doped zinc sulfide, the proportions of Fe, Zn, and S atoms are 5-8%, 47-50%, and 44-46%, respectively.
[0036] Doping with zinc sulfide increases the intrinsic conductivity of ZnS, reduces the activation energy of the electrochemical reaction, and generates a large number of S vacancies to induce a built-in electric field, accelerating K +The diffusion rate in the negative electrode material is improved, thereby improving the specific capacity and charge-discharge rate performance of the battery when it is used as the negative electrode of potassium ion batteries. In addition, the optimized ZnS realizes the redistribution of charges around the metal-sulfur bond, increases the bond energy of the Zn-S bond and stabilizes the ZnS lattice structure, greatly alleviating the problem caused by large K + The inhomogeneous internal mechanical stress caused by embedding alleviates the capacity degradation problem caused by lattice collapse and ensures the cycle stability.
[0037] The present application also provides a potassium ion battery, wherein the negative electrode material is prepared by replacing the zinc sulfide negative electrode material with iron atoms in the potassium ion battery in the above embodiment, and has a hollow spherical morphology and a diameter of 550-650nm. The carbon encapsulation strategy formed by amino acid annealing effectively improves its conductivity, and its stable hollow structure effectively alleviates the mechanical strain stress generated during potassium storage, thereby improving its structural stability during potassium storage, and achieving excellent long-cycle stability even at high rates.
[0038] In one embodiment, the preparation method further includes step S4, which includes: preparing a polyaniline ethanol solution with a concentration of 5%-10%wt, mixing the iron atom substituted-zinc sulfide negative electrode material and the polyaniline ethanol solution at a weight ratio of 1:20-1:25, stirring for 2-3 hours and simultaneously performing ultrasonic treatment, centrifuging the mixed solution, collecting the coated powder, washing and drying to obtain the polyaniline-coated iron atom substituted-zinc sulfide negative electrode material. Since the outer layer is coated with polyaniline, the material has better conductivity and can effectively enhance its mechanical strength.
[0039] The technical solution of the present invention is further described below by specific implementation methods. The models and manufacturers of the instruments used in the following examples and comparative examples are:
[0040] Vacuum drying oven, DZF-250, Beijing Yongguangming Medical Instrument Co., Ltd.; tube furnace, Hefei Kejing Material Technology Co., Ltd.; coating machine, AFA-1, Hefei Kejing Material Technology Co., Ltd.; glove box, MB-Labstar, Braun Inert Gas (Shanghai) Co., Ltd.; battery testing system, CT2001A, Wuhan Blue Electric Electronics Co., Ltd.; electrochemical workstation, V54829, Ivium (Netherlands).
[0041] Embodiment 1:
[0042] 60 mg of ammonium ferric citrate and 1.5 g of L-cysteine were added to 50 ml of deionized water and stirred magnetically until transparent to form solution A;
[0043] Dissolve 2.97 g of zinc nitrate hexahydrate in 100 ml of deionized water and mix evenly under magnetic stirring to form solution B;
[0044] Dissolve 6.56 g of dimethylimidazole in 100 ml of deionized water and mix evenly under magnetic stirring to form solution C;
[0045] Under continuous stirring, solution A and solution B were quickly added to solution C. After the mixed solution was stirred for 2 h, it was placed at room temperature for aging for 3 days.
[0046] The aged suspended particles were collected by centrifuge, washed with deionized water and ethanol three times respectively, and freeze-dried to obtain the precursor powder;
[0047] The precursor powder was placed on a magnetic boat and placed in a tube furnace filled with argon at 2 °C min -1 The sample was annealed at a heating rate of 550 °C and kept at that temperature for 2 h. The sample was then heated to 800 °C and kept at that temperature for 2 h. After naturally cooling to room temperature, black Fe-ZnS@C powder was obtained.
[0048] The obtained negative electrode material was tested by electron scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The SEM images obtained by the test are shown in Figure 1 , transmission electron microscopy image is shown in Figure 2 , please refer to Figure 1-2 , Fe-ZnS@C presents a uniform and clear unique hollow spherical structure, and the average diameter of each spherical structure is about 600 nm. Figure 2 It can be clearly observed that there is a clear cavity inside the sphere, and Fe-ZnS@C with a hollow spherical structure is obtained. Figure 2 The electron diffraction pattern in confirms that the obtained material is in good agreement with the theoretical (010), (-100) and (1-10) crystal planes of ZnS on the
[001] band axis, and is a crystalline ZnS material.
[0049] Please refer to Figure 3 , Figure 3 It shows that in the Fe-ZnS@C material, Fe, Zn, S, C and N elements are evenly distributed, and C and N elements show brighter brightness than other elements in the outer layer of the spherical shell, indicating that their content in the outer layer of the spherical shell is higher, that is, the nitrogen-doped carbon layer is evenly coated outside the spherical shell, and it is calculated that the Fe, Zn and S atoms in the Fe-ZnS@C obtained in Example 1 account for 5.2%, 49.2% and 45.6% respectively.
[0050] Figure 4 The synchrotron radiation confirmed wavelet transform (WT) analysis contour map of the Fe-ZnS@C material of Example 1 shows high resolution in both R and k space. -1The maximum intensity of Fe was observed at k = 5.3 Å, while Fe-ZnS@C showed a significant negative shift at k = 5.3 Å. -1 The synchrotron radiation experimental data confirmed the existence of Fe atoms in the +2 valence form and the existence of Fe-S bonds in the ZnS lattice.
[0051] Embodiment 2:
[0052] The only difference between this embodiment and embodiment 1 is that solution A includes 90 mg of ammonium ferric citrate, and other conditions and parameters are exactly the same as those in embodiment 1.
[0053] Embodiment 3:
[0054] The only difference between this embodiment and embodiment 1 is that solution A includes 120 mg of ammonium ferric citrate, and other conditions and parameters are exactly the same as those in embodiment 1.
[0055] Embodiment 4:
[0056] The difference between this embodiment and embodiment 1 is that the precursor powder is placed in a tube furnace filled with argon gas at 2°C min -1 The sample was annealed at a heating rate of 500°C to 550°C, kept at that temperature for 2 h, and then heated to 700°C. Other conditions and parameters were exactly the same as those in Example 1.
[0057] Embodiment 5:
[0058] The difference between this embodiment and embodiment 1 is that the precursor powder is placed in a tube furnace filled with argon gas at 2°C min -1 The sample was annealed at a heating rate of 500°C to 550°C, kept at that temperature for 2 h, and then heated to 1000°C. Other conditions and parameters were exactly the same as those in Example 1.
[0059] Example 6
[0060] In this embodiment, the Fe-ZnS@C prepared in Example 1 is coated with conductive polyaniline (PANI, CAS: 5612-44-2) in the following steps:
[0061] Prepare a PANI ethanol solution with a concentration of about 5%wt, evenly disperse 1g of Fe-ZnS@C powder in 20ml of PANI ethanol solution, stir for 2 hours and perform ultrasonic treatment (80W, 40kHz ultrasonic machine) at the same time to make PANI evenly cover the surface of the powder. After stirring, the mixed solution is separated by centrifugation to collect the coated powder. Wash with deionized water and ethanol three times respectively to remove excess solvent and unreacted PANI. Place the washed powder in an oven and dry at 50°C until the water is completely removed to obtain PANI@Fe-ZnS@C.
[0062] Comparative Example 1:
[0063] The only difference between this embodiment and embodiment 1 is that solution A does not include L-cysteine, and other conditions and parameters are exactly the same as those in embodiment 1.
[0064] Comparative Example 2:
[0065] The only difference between this embodiment and embodiment 1 is that 50 ml of deionized water is mixed with solution B and solution C to obtain a precursor solution, and the precursor is mixed with sulfur powder in a mass ratio of 1:3 and then annealed. Other conditions and parameters are exactly the same as those in embodiment 1.
[0066] Performance Testing:
[0067] 8 parts by weight of the negative electrode materials obtained in Examples 1-5 and Comparative Examples 1-2, 1 part of superconducting carbon and 1 part of a binder (preferably CMC) were mixed and dissolved and dispersed in a mixed solution of ethanol / water to obtain a negative electrode slurry; the negative electrode slurry was heated to 0.8 mg cm -2 The negative electrode sheet was combined with a counter electrode potassium block and a separator (GF / A (Whatman)), and an electrolyte 5 M KFSI in DEGDME was added and assembled into a battery casing to obtain a battery.
[0068] Battery performance test method:
[0069] Cyclic performance test: Using the Wuhan Blue Electric test system in China, the constant current charge and discharge (GCD) curve of the battery was tested at a constant temperature of 28°C. The battery was discharged to 0.01 V at a current density of 100 mA / g, and then charged to 3.0 V at a current density of 100 mA / g. This was recorded as the first cycle, and the first reversible capacity D1 and the first coulombic efficiency were recorded. The aforementioned charge and discharge process was repeated, the reversible capacity Dn of the nth cycle was recorded, and the capacity retention rate of the nth cycle was calculated.
[0070] Rate cycling performance: The constant current charge and discharge (GCD) curve of the battery was tested using the Wuhan Blue Electric Test System in China. The battery was discharged to 0.01 V at current densities of 100, 200, 300, 500, 800, 1000, 2000 and 3000 mA / g, and then charged to 3.0 V at the same current density, and 10 cycles were repeated at each current density.
[0071] After the assembled battery was left to stand for 12 h, the electrochemical performance test was performed with the voltage window set to 0.01-3 V. The test results are shown in the following table:
[0072] Table 1:
[0073]
[0074] As shown in Table 1, the cycle performance at a current density of 100 mA / g shows that the reversible specific capacity of the iron atom-substituted zinc sulfide negative electrode material of Example 1 can reach 583.9 mAh g after 240 cycles. -1 The specific capacity decay rate of each cycle is only 0.019%. In contrast, the reversible specific capacity of comparative example 1 after 240 cycles is only 229.9 mAh g -1 , the specific capacity decay rate of each cycle of Comparative Example 2 is as high as 0.26%. The reason for the poor performance of Comparative Example 2 is that the shuttle effect of polysulfide intermediates is serious, resulting in poor integrity of the electrode structure. The electrochemical performance of Example 1 proves that the substitution strategy not only improves the conductivity of sulfides, but also stabilizes the intercalation reaction in potassium ion batteries and promotes the conversion reaction in potassium ion batteries, so that potassium ion batteries exhibit high specific capacity and high reversibility. Intercalation reaction refers to the process in which potassium ions are reversibly embedded in or out of the lattice structure of negative and positive electrode materials during the charge and discharge process. Conversion reaction refers to the process in which potassium ions react chemically with electrode materials to generate new compounds during the charge and discharge process.
[0075] It is worth noting that the PANI@Fe-ZnS@C provided in Example 6 exhibits good cycle performance when applied to the negative electrode material of potassium ion batteries, and the reversible specific capacity reaches 626.9 mAh g after 240 cycles. -1 After PANI coating Fe-ZnS@C, the conductivity of the material is effectively improved, the internal resistance of the material is reduced, and the electrochemical performance of the electrode material is enhanced. At the same time, PANI provides more electrochemical active sites, improves the capacity and efficiency of the material, and also increases its mechanical stability. Coating the hollow spherical Fe-ZnS@C can effectively enhance its mechanical strength and avoid the collapse of the hollow spherical structure, so it can improve its cycle stability, prevent structural damage during the charge and discharge cycle, and extend the life of the battery.
[0076] See also Figure 5 , Figure 5 The scanning electron microscope image of PANI@Fe-ZnS@C is shown. Figure 5 It can be seen that the protrusions on the surface of the coated Fe-ZnS@C material have been covered by polyaniline, and the surface has become significantly smoother. The coating layer also improves the interfacial interaction between the material and the electrolyte, reduces the interfacial impedance, enhances the ion transfer efficiency, and makes the overall battery performance more excellent. Overall, after polyaniline coating, the Fe-ZnS@C composite material exhibits higher conductivity, stability and electrochemical activity in battery applications, becoming a better electrode material. Test data also show that its capacity and cycle stability have been improved.
[0077] Please refer to Figure 6-7 , Figure 6 The figure shows the rate cycle performance of the battery made of the negative electrode materials of Example 1 and Comparative Example 2 of the present application, Figure 7 The high current density cycle performance diagram of the battery made of Fe-ZnS@C in Example 1 of the present application is shown.
[0078] The partial atomic substitution strategy in a single transition metal chalcogenide in Example 1 is beneficial to improving the intrinsic conductivity and ion diffusion rate of the electrode, thereby improving the rate performance and specific capacity at high current density of Example 1. Comparative Example 2 has poor rate performance due to the poor intrinsic conductivity of zinc sulfide.
[0079] Please continue to refer to Figure 8 , Figure 8 The full-cell rate performance diagram of the battery made of Fe-ZnS@C in Example 1 of the present application is shown. In Example 1, since the atomic substitution strategy improves the conductivity and lattice stability of the sulfide, it obtains good full-cell rate performance and better reversibility of the full battery. The excellent energy density and cycle stability of Example 1 indicate that it has the potential for practical application.
[0080] In addition, the description of the terms "some embodiments", "other embodiments", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In the present application, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine the different embodiments or examples described in the present application and the features of the different embodiments or examples without contradiction.
[0081] The above implementation modes are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned implementation modes, a person skilled in the art should understand that the technical solutions described in the aforementioned implementation modes can still be modified, or some of the technical features can be replaced by equivalents. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various implementation modes of the present application, and should all be included in the protection scope of the present application.
Claims
1. A method for preparing an iron atom-substituted zinc sulfide negative electrode material, characterized in that: include: S1: Mix ammonium ferric citrate, L-cysteine and deionized water to form solution A, wherein the concentration of ammonium ferric citrate in solution A is 2-5 mmol / L -1 , the concentration of L-cysteine is 0.24-0.3 molL -1 The hexahydrated zinc nitrate and deionized water were mixed to form a solution B, wherein the concentration of the hexahydrated zinc nitrate in the solution B was 90-100 mmol / L -1 The dimethylimidazole and deionized water were mixed to form a solution C, wherein the concentration of dimethylimidazole in the solution C was 0.6-0.7 molL -1 ; S2: uniformly mixing the solution A, the solution B and the solution C in a weight ratio of 1:2:2-1.5:2:2 to obtain a precursor solution, and collecting a precursor powder after centrifuging the precursor solution; S3: annealing the precursor powder at 700-1000° C. for 2-4 h under an inert atmosphere to obtain the iron atom-substituted zinc sulfide negative electrode material; S4: prepare a polyaniline ethanol solution with a concentration of 5%-10%wt, mix the iron atom substituted-zinc sulfide negative electrode material and the polyaniline ethanol solution in a weight ratio of 1:20-1:25, stir for 2-3 hours and perform ultrasonic treatment at the same time, separate the mixed solution by centrifugation, collect the coated powder, wash and dry to obtain the polyaniline-coated iron atom substituted-zinc sulfide negative electrode material.
2. The preparation method according to claim 1, characterized in that: The inert atmosphere in step S3 is an argon atmosphere or a nitrogen atmosphere.
3. The preparation method according to claim 1, characterized in that: Step S3 includes heating the precursor powder in an argon atmosphere at 2-5°C min -1 The temperature is increased to 500-550°C and kept at this temperature for 2-4 hours, and then increased to 700-1000°C and kept at this temperature for 2-4 hours.
4. The preparation method according to claim 1, characterized in that: The step S2 further includes uniformly mixing the solution A, the solution B and the solution C in a weight ratio of 1:2:2-1.5:2:2 to obtain the precursor solution, continuing stirring for 1-2 hours, and aging at room temperature for 3-5 days.
5. An iron atom substituted zinc sulfide negative electrode material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 4, the iron atom substituted-zinc sulfide negative electrode material comprises nitrogen-doped carbon-coated doped zinc sulfide, and the doped zinc sulfide comprises zinc sulfide and iron atom-doped zinc sulfide.
6. The iron atom substituted zinc sulfide negative electrode material according to claim 5, characterized in that: The iron atom substituted zinc sulfide negative electrode material has a hollow spherical morphology and a diameter of 550-650 nm.
7. The iron atom substituted zinc sulfide negative electrode material according to claim 5, characterized in that: In the doped zinc sulfide, Fe, Zn and S atoms account for 5-8%, 47-50% and 44-46% respectively.
8. The iron atom substituted zinc sulfide negative electrode material according to claim 5, characterized in that: The nitrogen-doped carbon-coated doped zinc sulfide outer layer is coated with polyaniline.
9. A potassium ion battery, characterized in that: The potassium ion battery comprises a positive electrode and a negative electrode, and the negative electrode of the potassium ion battery is prepared from the iron atom substituted-zinc sulfide negative electrode material according to any one of claims 5 to 8.
Citation Information
Patent Citations
Preparation method of Fe-doped ZnS-CuS heterojunction photocatalytic hydrogen production material
CN112517028A
Preparation method of zinc sulfide / nitrogen-doped carbon composite material for negative electrode of lithium ion battery
CN116544375A